A case report of Posterior reversible encephalopathy syndrome with spinal cord involvement (PRES-SCI), an atypical presentation of PRES in children. : (A case report and review of literature) - Akhondian, Javad; Ashrafzadeh, Farah; Seilanian Toosi, Farrokh; Behnam, Mahdi; Imannezhad, Shima; Akhoundian, Mohammad Reza; Hashemi, Narges; Beiraghi Toosi, Mehran (Iranian Journal of Child Neurology, 2022)
Abstract Posterior reversible encephalopathy syndrome has a broad spectrum in clinical presentation and radiologic features. Diagnosis of posterior reversible encephalopathy syndrome (PRES) based on reversible clinical manifestations and sequential neuroimaging. Atypical MRI features were defined as hemorrhage, restricted diffusion or contrast enhancement of lesions, involvements of temporal and frontal lobes, brain stem, basal ganglia, corpus callosum, cerebellum, and spine. Atypical PRES with or without spinal cord involvement is a rare presentation, especially in children. Up to 2020, just 5 cases of posterior reversible encephalopathy syndrome with spinal cord involvement (PRES-SCI) have been published in pediatrics. Case report Here we describe the youngest patient that has been reported, with the diagnosis of PRES-SCI. All of 6 cases had high signal intensities on T2 weighted images in the brain stem and cervical cord that in fallow up the brain and spinal MRI, had been completely resolved. All the patients had hypertension in the base of renal disease except one girl with chemotherapy-induced hypertension. Headache, altered mental status, seizure, and visual impairment were the most common symptoms respectively. Facial palsy was a remarkable warning sign in some patients before admission. PRES-SCI is rare in pediatrics but since it is reversible, prompt diagnosis and management can change the prognosis in these children. Keywords: Posterior reversible encephalopathy syndrome, Spinal cord, Hypertension, Pediatrics